2001
DOI: 10.1159/000054899
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Intranasally Administered Cholecystokinin-8 on Central Nervous Effects

Abstract: The gut and brain peptide cholecystokinin (CCK) exerts a number of central nervous effects. Among them are effects on attention and stimulus processing as revealed by modulations of event-related potentials (ERPs). In the present study the time course of central nervous effects after an intranasal administration of CCK-8 was investigated by means of ERPs. ERPs were recorded in an oddball paradigm 15, 30, 60, 90, 120, and 240 min after administration. Following the double-blind intranasal administration of CCK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Similar results were obtained by the same group after nasal and intravenous administration of cholecystokinin-8 (Pietrowsky et al 1996b) and performance of an auditory attention task (oddball task) in 20 volunteers in a double blind cross-over study recording the auditory event-related brain potentials. Further studies confirmed the results (Pietrowsky et al 2001).…”
Section: Human Studiessupporting
confidence: 79%
“…Similar results were obtained by the same group after nasal and intravenous administration of cholecystokinin-8 (Pietrowsky et al 1996b) and performance of an auditory attention task (oddball task) in 20 volunteers in a double blind cross-over study recording the auditory event-related brain potentials. Further studies confirmed the results (Pietrowsky et al 2001).…”
Section: Human Studiessupporting
confidence: 79%
“…From these data, two 'general rules' emerge: after IN-administration: (1) brain/CSF-levels tend to be higher than the peripheral levels, sometimes higher than the levels obtained after i.v.-administration; (2) peripheral levels rise more slowly and are generally preceded by steeper rising brain/CSF-levels. Such effects have been shown for neuropeptides and hormones like CCK-8 (Pietrowsky et al, 2001(Pietrowsky et al, , 1996, vascular endothelial growth factor (VEGF) , MSH/ACTH (Born et al, 2002), insulin-like growth factor-1 (Thorne et al, 2004) and hexarelin (Yu and Kim, 2009), as well as for a variety of other substances like testosterone (Banks et al, 2009), estradiol (Ohman et al, 1980;Wang et al, 2006), ergoloid mesylate , gastrodin (Wang et al, 2007, cephalexin (Sakane et al, 1991), tetramethylpyrazine (Feng et al, 2009), and the angiotensin antagonist GR138950 (Charlton et al, 2008). This list can be extended easily but these suffice to illustrate that INadministration of substances mostly results in faster peaks and/or higher brain concentrations than peripheral administration.…”
Section: Ot-levels After In-ot In Cerebrospinal Fluid (Csf) and Bloodmentioning
confidence: 81%
“…Occasionally, in human studies, the behavioral effects of IN-OT were studied after about an hour (Burri et al, 2008). However, plasma levels of OT were elevated already within 20 min (Burri et al, 2008;Landgraf, 1985), whereas the central nervous effects of a neuropeptide of similar size (cholecystokinin, CCK-8, MW 1143) were most clearly obtained at 15-30 min after IN-administration (Pietrowsky et al, 2001). The finding that plasma OT-levels remain elevated for a long time (more than 80 min!)…”
Section: Entrance Routes and Distribution Of In-otmentioning
confidence: 99%
“…AEPs were measured 45 min after substance administration while the subjects performed an oddball task in a sound-attenuated and electrically shielded room. The time of drug administration was chosen based on foregoing results in healthy subjects although more recent data indicate that a more delayed AEP recording would have been preferable (Pietrowsky et al 1996b(Pietrowsky et al , 2001. The task stimuli were 200 tone pips (60 ms duration) binaurally presented via headphones (beyerdynamic DT48, 800 Ω, Germany) at an intensity of 60 dB SPL.…”
Section: Design and Proceduresmentioning
confidence: 99%